(untitled) (Journal of the College of Basic Education, 2022)
The sport of fencing requires the speed of movement in the field and the muscular ability of the upper and lower extremities during progress and retreat and the skill of stabbing. Hence the importance of research lies in the interest in accuracy in stabbing because of its importance on the outcome of the competition, which requires special physical capabilities, so all coaches should pay attention to these skills and try developed.The research aimed to prepare a training curriculum that suits the capabilities of the research sample and to identify the extent of the impact of the proposed curriculum on developing some physical abilities and the skill of the challenge. And then identify the relationship between some special physical abilities and the stabbing skill of female fencing players.The experimental method was used due to its suitability to the nature of the study, while the sample was chosen by the intentional method, as it included female players from the fencing team in the girl’s club, and their ages ranged between (20-24) years.